Research on the Influence Effect of Digital Economy on Urban-Rural Integration Development: Based on Provincial Panel Data Empirical Analysis - Gao, Jiajia (International Journal of Global Economics and Management, 2024)
As socialism with Chinese characteristics enters a new era, the problem of unbalanced and insufficient development in China remains prominent at this stage. In the Vision 2035, "strengthening digital development" and achieving "agricultural modernization" and "significantly narrowing the development gap between urban and rural areas and the gap between the living standards of the population" will coincide with each other. The digitalization of urban-rural integration is both an opportunity and a challenge. This project focuses on the impact of digital economy development on urban-rural integration. Based on the panel data of 31 provinces in China from 2010 to 2020, we conduct a systematic research on the impact of digital economy on urban-rural integration development, focusing on the three dimensions of theoretical analysis, empirical measurement and mechanism. Firstly, we reveal the spatial and temporal evolution of China’s digital economy development; secondly, we conduct theoretical analysis through literature review and model construction; thirdly, we construct the index system of digital economy and urban-rural integration level and measure the level of urban-rural integration development; we adopt the random effect and fixed effect models to test the direct impact of digital economy development level on urban-rural integration development, and utilize the mediation effect model to validate the effect mechanism of digital economy on urban-rural integration; finally, we propose that digital economy contributes to the development of urban-rural integration. mechanism; and finally put forward the suggestions for digital economy to boost the high-quality development of urban-rural integration, with a view to realizing the development of rural digital economy and promoting urban-rural integrated development.